Students’ Vocabulary Knowledge: Comparative Study Enhancing Between Semantic Mapping and Diglot Weave Techniques - Simanjuntak, Olivia Virocky; Simanjuntak, Debora Chaterin (LPPM Universitas Advent Indonesia, 2018)
The purpose of this study is to find out whether there is any significant difference between Semantic Mapping and Diglot Weave Techniques in enhancing the students’ vocabulary knowledge. This study is quantitative, utilizing comparative research design,a simple research design which is used to examine two techniques of teaching. In this study, the researcher treated two groups with two different techniques: Semantic Mapping and Diglot Weave. Each technique is deemed to be comparable in enhancing students’ vocabulary knowledge. On the basis of the target this study, the researcher has to decide which technique that is more effective in enhancing students’ vocabulary knowledge. The researcher found out that there is significant difference between group that was taught using Semantic Mapping technique and group that was taught using Diglot Weave Technique in enhancing students’ vocabulary knowledge. In fact, the group that acquired Diglot Weave Technique had higher gain of score than the group that acquired Semantic Mapping.Keyword - Semantic Mapping Technique, Diglot Weave Technique, Vocabulary Knowledge